Curcuma longa L. Effects on Akt/mTOR Pathway and NF-κB Expression During Skin Wound Healing: An Immunohistochemical Study. Issue 10 (November 2021) - Danilevicz, Chris K.; Wagner, Vivian P.; Ferreira, Nilson; Bock, Hugo; Salles Pilar, Emily F.; Webber, Liana P.; Schmidt, Tuany R.; Alonso, Ellen C.P.; de Mendonça, Elismauro F.; Valadares, Marize C.; Marreto, Ricardo N.; Martins, Manoela D.
Abstract : Skin ulcers, wounds, or burns represent a burden for health care worldwide. Our aim was to explore the effects of mucoadhesive formulation with Curcuma longa L. extract mucoadhesive formulation containing curcumin (MFC) on skin healing in Wistar rats. Fifty-four rats were randomly allocated into 3 groups: control, vehicle, and MFC. A full-thickness circular wound was induced on the back of each animal. Two daily applications of the products were performed according to the experimental group. On days 3, 10, and 21, 6 animals in each group were euthanized. Clinical analysis was based on wound area. Histologic analysis was performed in hematoxylin and eosin-stained sections, with re-epithelization and inflammation being assessed by means of semiquantitative scores. To analyze the Akt/mTOR pathway, immunohistochemistry for phospho Akt (pAkt) and phospho ribosomal protein S6 were investigated. In addition, nuclear factor kappa-light-chain-enhancer of activated B cells immunolabeling was performed. Clinical analysis revealed wounds with a smaller area on days 3 and 10 in curcumin-treated animals. Histologically, MFC had a significant impact on inflammatory events on days 3 and 10 and promoted faster re-epithelization, which was evidenced on day 10. MFC-treated wounds exhibited pAkt upregulation on day 10 and both pAkt and phospho ribosomal protein S6 downregulation on day 21. Nuclear factor kappa-light-chain-enhancer of activated B cells expression varied through the evaluation periods; however, no significant difference was observed between groups. Collectively, our results indicate that MFC is efficient in accelerating cutaneous wound repair through modulation of the inflammatory process and stimulus of re-epithelization by an Akt/mTOR-dependent mechanism. Abstract : Supplemental Digital Content is available in the text.